Pelatihan melalui Web Seminar terkait Publikasi Artikel untuk Menembus Jurnal Sinta 2 dan Scopus - Firmansyah, Amrie; Qadri, Resi Ariyasa; Arham, Amardianto (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2020)
This community service activity aims to provide training for lecturers and students in producing journal articles that can be submitted for publication in the Sinta 2 journal and Scopus journal. This activity was carried out through a web seminar due to the condition of the Covid-19 pandemic which made it impossible to conduct conventional training. Organizers of this activity are Pamulang University and Bina Insani University. This activity was attended by lecturers and students from DKI Jakarta, West Java, Central Java, East Java, Bali and East Kalimantan. The method of carrying out this activity consists of several stages. The first stage is the planning stage through discussion with the organizers to meet the expectations of participants regarding the benefits of this activity. The second stage is the delivery of material and discussion through web seminar via Zoom application and Google Meet. The third stage is further online discussion with participants who need additional explanations. Based on feedback obtained from the participants, this activity is very useful for participants and motivates participants to improve the quality of research articles so that they can be submitted for publication in the Sinta 2 journal and Scopus journal.DOI:Â https://doi.org/10.26905/abdimas.v5i2.4244